18‐4: MicroLED Displays based on Transfer with Microtubes Interconnections. Issue 1 (29th May 2019) - Bernard, Jeannet; Haas, Helge; Caplet, Stéphane; Bedoin, Alexis; Tournaire, Myriam; Peray, Patrick
Abstract : We have fabricated blue and green microLED display prototypes. The microLEDs have been transferred using microtube technology. The interest of microtube for large area microLED displays has been demonstrated by providing both mechanical and electrical connection. Overall, this technology brings a lot of advantages compared to existing solutions.